Financial Navigation: Building Generation Z Literacy through Learning Channels - Mu’afi, Muhammad Irfan; Hapsari, Nurul Retno; Amalia, Tazkia; Jesie, Titan Aprista (Jurnal Ilmu Komunikasi, 2025)
This research aims to explore the role of learning channels in enhancing financial literacy among Generation Z. Given the increasingly complex financial challenges in the digital era, financial literacy is becoming an essential skill to possess. This study employs a quantitative approach using questionnaires with active university students from the 2019-2022 cohorts aged 18-22 years as research subjects. The learning channels used as indicators in this study are: family / friends, social media, formal education, influencers, investment apps, and non-formal education. The data obtained were analyzed using Smart-PLS. The results of this study indicate that learning channels with the indicators of family, social media, formal education, and investment apps have a significant impact on financial literacy, whereas influencers and non-formal education do not significantly affect financial literacy. These findings suggest that financial literacy among Generation Z can be effectively improved through structured and relevant learning channels, particularly those integrated into daily life and formal education settings.